Menimbang Definisi Seni dalam Estetika - Deni Junaedi (EKSPRESI, 2010)
Rethinking Art Definition in Aesthetic Field. In the aesthetic definition of art, an object is an art, and only if it is produced with the intention that it possessed a capacity of affording aesthetic experience. Aesthetic experience refers to some mental states that a spectator brings to or undergoes in responding to artworks. Two major accounts of aesthetic experience are the affect-oriented accounts. The affect-oriented accounts are marked by disinterestedness, empathy, and contemplation. The content-oriented accounts can be sorted under three broad headings: unity, diversity, and intensity. If the aesthetics definition of art can be examined for all artworks, the definition is correct; otherwise, if the aesthetics definition of art cannot be examined for all artwork, the definition is incorrect. Keywords: aesthetic experience; art definition